Fresh approaches to antidepressant drug discovery. (April 2014) - Anacker, Christoph
<x xml:space="preserve">Abstract</x> Introduction: The success of antidepressant research has long been challenged by a limited mechanistic understanding of depression pathogenesis and antidepressant treatment response. Progress in this field has thereby consistently been hindered by a lack of novel conceptual approaches and sophisticated experimental techniques to dissect the highly intricate neurobiology of depression. Using fresh approaches to investigate the cellular and molecular mechanisms underlying depression will thus be vital for discovery of novel antidepressant targets. Areas covered: This article provides an overview of some fundamental problems that depression research is currently facing and critically evaluates how these issues could be addressed by future research. It also discusses novel conceptual and technological advances in the field of neuroscience, particularly in regard to how they may help in providing unprecedented insight into the molecular mechanisms of depression pathogenesis. Expert opinion: Although progress in antidepressant drug discovery has been limited over recent years, modern innovations in neuroscience, molecular biology, genetics and bioinformatics are just beginning to revolutionize depression research and to reveal novel and promising treatment targets. Integrating findings from a range of relevant experimental models and using the most advanced technology will be vital for the future success of antidepressant drug discovery.